Human immunodeficiency virus seroprevalence in children received multiple transfusions or blood products in the Department of Child Health Faculty of Medicine University of Indonesia/Dr. Cipto Mangunkusumo General Hospital, Jakarta - C. S. Matondang; Arwin Akib; Syawitri P. Siregar; Maria Abdulsalam; Jeanne Latu; Farida Oesman; Erwin Silman (Paediatrica Indonesiana, 1988)
From March 1987 till February 1988, 350 serological examinations to HJV antibodies have been carried out. Sera were taken from children visiting the Department of. Child Health Faculty of Medicine University of Indonesia I Dr. Cipto Mangunkusumo General Hospital, Jakarta, who had received blood or blood products transfusions more than three times. All blood or blood products were made locally by the Jndonesian Red Cross in Jakarta, except for Human immunoglobulin and Koate. The age ranged from 9 months Ia 22 years with a mean age of 8,02 years. They consisted of 207 males and 143 females; 33 patients with hemophilia, 250 patients with thalassemia, 41 patients with blood malignancy, and 26 patients with other diseases. Sera were tested by a commercially available ELISA HIV assay produced by Abbott (macro ELISA) and Behring (micro ELISA). Repeatable positive sera were confirmed by Western blatt. The majority of patients in this study got their first transfusion on more than 5 years ago with a high consumption of blood components, namely 16.252 units of packed red cells, 6111 units of cryoprecipitate, 537 units of thrombocyte suspension, 96 units of fresh frozen plasma, 35 units of human immunoglobulin, and 15 vials of Koate. Two out of 350 sera were repeatable positive for HIV antibody but confirmatory test by Western blatt were negative. One sera was from a 17-year-o/d gM with thalassemia who had received 129 units of packed red cells transfusions since 1979, and the other was from a 2-year-o/d girl with chronic myelocytic leukemia who had received 24 units of packed red cells. The rest of the sera were negative. This zero prevalence finding suggests that in Indonesia transfusion of blood or blood products still plays a limited role in the epidemic of AIDS in children.